The Development of Video Podcast as an Innovation in Online Nutrition Education and Its Engagement Data Analysis - Sholihah, Lini Anisfatus (UI Scholars Hub, 2022)
Podcasts have become more popular in Indonesia recently. Studies have shown that video podcasts, which incorporate education and entertainment aspects, are effective as a medium to study language and medical subjects among students and clinicians. This study aims to analyze video podcasts’ utilization in nutrition education and how they can engage viewers from the general community. This paper further aims to describe the development of a video podcast, NutriPodcast, as an innovative media to educate the community regarding nutrition topics. The number of audience views was calculated by utilizing the analytical feature on social media. The methodology to develop the podcast consisted of three stages: design, edit, and distribution. The design stage of the podcast refers to planning the style and length of the podcast and determining the media to be used. The editing stage includes both technological and technical aspects, such as hardware and software equipment. YouTube was chosen as the platform to upload the video podcast. The number of views of the podcast on YouTube was comparable to that of another previous podcast research. Most viewers used smartphones to access video podcasts. People from the 25–34 age group (55.2%) and females (51.5%) made up more than half the proportion of the viewers. It can be concluded that a video podcast provides an opportunity to facilitate a community seeking nutrition and health information.